The Comstocks of Cornell John Henry Comstock and Anna Botsford Comstock - Comstock, Anna Botsford (Cornell University Press, 2019)
The Comstocks of Cornell is the autobiography written by naturalist educator Anna Botsford Comstock about her life and her husband's, entomologist John Henry Comstock-both prominent figures in the scientific community and in Cornell University history. A first edition was published in 1953, but it omitted key Cornellians, historical anecdotes, and personal insights. Karen Penders St. Clair's twenty-first century edition returns Mrs. Comstock's voice to her book by rekeying her entire manuscript as she wrote it, and preserving the memories of the personal and professional lives of the Comstocks that she had originally intended to share. The book includes a complete epilogue of the Comstocks' last years and fills in gaps from the 1953 edition. Described as serious legacy work, the book is an essential part of Cornell University history and an important piece of Cornell University Press history.